The Gateway to Computer Science Excellence
First time here? Checkout the FAQ!
x
+2 votes
48 views

Consider the code below, defining the function $A$:

A(m, n, p) {
    if (p == 0) return m+n;
    else if (n == 0 && p == 1) return 0;
    else if (n == 0 && p == 2) return 1;
    else if (n == 0) return m;
    else return A(m, A(m,n-1,p), p-1);
}

Compute $A(2, 2, 3)$ and $A(2, 3, 3)$.

asked in Algorithms by Veteran (96.1k points) | 48 views

Please log in or register to answer this question.

Related questions

Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true
49,541 questions
54,083 answers
187,206 comments
70,992 users